Inhibition of early development stages of rust fungi by the two fungal metabolites cyclopaldic acid and epi‐epoformin. Issue 6 (16th November 2016) - Barilli, Eleonora; Cimmino, Alessio; Masi, Marco; Evidente, Marco; Rubiales, Diego; Evidente, Antonio
Abstract: BACKGROUND: Rusts are a noxious group of plant diseases affecting major economically important crops. Crop protection is largely based on chemical control. There is a renewed interest in the discovery of natural products as alternatives to synthetic fungicides for control. In this study we tested two fungal metabolites, namely cyclopaldic acid and epi ‐epoformin, for their effectiveness in reducing early stages of development of two major rust fungi from the genera Puccinia and Uromyces, P. triticina and U. pisi . Spore germination and appressorium formation were assessed on pretreated detached leaves under controlled conditions. Cyclopaldic acid and epi ‐epoformin were also tested in infected plants in order to evaluate the level of control achieved by treatments both before and after inoculation. RESULTS: Cyclopaldic acid and epi ‐epoformin were strongly effective in inhibiting fungal germination and penetration of both rust species studied. This effect was not dose dependent. These results were further confirmed in planta by spraying the metabolites on plant leaves, which reduced fungal developmental of U. pisi and P. triticina at values comparable with those obtained by application of the fungicide. CONCLUSION: Our results further demonstrate the potential of fungal metabolites as natural alternatives to synthetic fungicides for the control of crop pathogens of economic importance as rusts. © 2016 Society of Chemical Industry